External spinal fixation of a lumbar fracture in a dog. Issue 4 (27th September 2021) - Poad, Lydia; Mielke, Benjamin; Ruiz De Alejos Blanco, Laura; Llabres‐Diaz, Francisco; De Decker, Steven
Abstract: An approximately 1‐year‐old female entire crossbreed dog presented for further assessment of a traumatically induced T3‐L3 myelopathy. CT demonstrated multiple vertebral fractures, a large paravertebral abscess with intracanal extension and an abdominal wall rupture. Given the active infection surrounding the lumbar fracture site, permanent internal fixation devices were deemed less favourable. An external skeletal fixator construct was placed using percutaneously placed positive profile pins and Steinmann pins as connecting bars. Repeat CT 8 weeks following surgery revealed good realignment of the vertebral column and resolution of the sublumbar abscess. The external fixator was removed and gradual return to exercise instructed over the following 8 weeks. This case report describes the use of an external vertebral skeletal fixator in a young dog with traumatic vertebral fracture when traditional methods were considered less favourable.